Comparison of Current Free Flap Options for Intraoral Lining and Tongue Reconstruction. Issue 7 (26th October 2022) - Gur, Ersin; Tiftikcioglu, Yigit Ozer; Ozturk, Kerem; Yegin, Mehmet Emre; Kuybulu, Turgut Furkan; Durukan, Kutay
Abstract : Free flaps have become the main alternative for intraoral reconstruction in current practice. However, controversy exists on pros and cons of different free flap options for this challenging area. Although there are various studies focusing on different free flap options, comparative studies are very few and there is not a single study comparing all 4 thin free flap options for intraoral reconstruction. Between 2018 and 2021, 30 patients underwent intraoral reconstruction. Four pliable and thin flaps, medial sural artery perforator flap, superficial circumflex iliac artery perforator flap, radial forearm free flap, and superthin anterolateral thigh flap were used for reconstructions and compared per functionality and patients' quality of life. One medial sural artery perforator flap and 1 superficial circumflex iliac artery perforator flap failed because of perfusion problems, and the remaining flaps survived. Harvest time and donor site closure were with significant difference ( P <0.05) between groups. Quality of life results were similar except one of the disease-specific questions. In authors' opinion, anterolateral thigh flap is the best option in normal-weight individuals because of its reliability, pliability, and constant reliable vascular structure. Although other options may be considered in overweighted patients, thinly elevated anterolateral thigh flap still seems to be the most reliable option.